The Potential of Antibodies Against the Phosphatidylserine / Prothrombin Complex as a Biomarker in Antiphospholipid Syndrome - Pasek, Piotr; Czyż, Witold; Kulbacka, Julia; Kacperczyk, Julia; Chuncia-Ileczko, Marta; Wójcikiewicz, Michalina; Arczewski, Filip; Dziedzic, Karol; Wojszczyk, Maciej; Zys, Damian; Ryniecka, Julia (Journal of Education, Health and Sport, 2025)
Introduction Antibodies against the phosphatidylserine/prothrombin complex aPS/PT are autoantibodies recognizing an epitope formed in the phosphatidylserine/prothrombin complex as a result of conformational changes resulting from the combination and not present in any of the initial components of the complex. Its presence is predominantly observed in patients with thrombotic complications, particularly in those suffering from antiphospholipid syndrome (APS), systemic lupus erythematosus (SLE), and other connective tissue disorders. The new epitope is clinically relevant, as it plays a role in the mechanism and effects of autoantibody binding to phospholipids and their cofactors. Testing for aPS/PT, in conjunction with other APS markers, is recommended to assess the risk of thrombotic events. Purpose The object of this review is to assess whether aPS/PT complex serves as an effective diagnostic marker in the pathogenesis of complications associated with APS and other connective tissue disorders. Material and methods This review evaluates data from medical databases such as PubMed, NCBI or BMJ using the search term ‘aPS/PT’. Conclusion The presence of aPS/PT may be considered an independent risk factor for thrombosis. However, further research is needed to fully validate its clinical relevance in various clinical scenarios.